Potential of Accurate Online Learning Platform Integration in University - Sidharta, Ervan; Kowinto, Susanti; Hidayat, Dylmoon (JKTP: Jurnal Kajian Teknologi Pendidikan, 2022)
In the 21st century, where technology develops rapidly, and during pandemic COVID-19 where distance learning relies on internet, online education technology in form of online learning platform has very big potential. University as education institution has the role to be the motor of innovation. Accurate integration of online learning platform is important to make sure all students, lecturers, and even the university itself to experience the benefit. This literature study aims to describe the accurate integration of online learning platform together with its potential caused by the accuracy, both positive and negative. It was found that by considering the learning objectives and strategies together with the capabilities of the students and lecturers, learning can be effective, creative, interactive, collaborative, meaningful, and valuable. The alumnus also equipped with 21st century skill and become a good digital citizen. Without accurate integration, learning activities will just waste the time and modals spent. Lecturers and students cannot perform optimally and can lead to depression. University also potentially only produce alumnus who are good intellectually but without good emotional intelligence. Online learning platform relies on internet and has a lot of features that must be integrated accurately to support learning.Abstrak Pada abad ke-21, teknologi berkembang dengan pesat, dan di tengah pandemi COVID-19 dimana pembelajaran jarak jauh menggunakan jaringan internet, teknologi pendidikan dalam bentuk platform pembelajaran daring memiliki potensi yang besar. Universitas menjadi sebagai institusi pendidikan bertugas menjadi motor penggerak inovasi. Integrasi platform pembelajaran daring yang akurat penting untuk memastikan para mahasiswa, dosen, sampai universitas itu sendiri merasakan manfaatnya. Studi literatur ini mendeskripsikan bagaimana mengintegrasikan platform pembelajaran daring secara akurat beserta potensi positif dan negatif sebagai akibat keakuratan tersebut. Ditemukan bahwa dengan mempertimbangkan tujuan dan strategi pembelajaran, juga kemampuan setiap dosen dan mahasiswa, pembelajaran dapat menjadi efektif, kreatif, interaktif, kolaboratif, bermakna dan bernilai. Para lulusan juga diperlengkapi dengan keterampilan abad-21 dan menjadi warga digital yang baik. Tanpa integrasi yang akurat, kegiatan pembelajaran akan menyita waktu sia-sia dan membuang-buang modal yang digunakan. Para dosen dan mahasiswa juga tidak dapat menunjukkan kinerja maksimalnya dan bahkan dapat berujung depresi. Universitas pun hanya menghasilkan mahasiswa yang hanya pintar secara intelektual tanpa kecerdasan emosional yang baik. Platform pembelajaran daring bergantung pada internet dan memiliki banyak fitur yang perlu diintegrasikan secara akurat untuk mendukung pembelajaran.